Glial Tumors of the Brain: General Principles of Diagnosis and Treatment (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Gliomas are the most common primary tumors of the central nervous system and represent a major medical and socio-economic problem due to their high incidence, malignant potential, and unfavorable prognosis. They account for up to 40–45% of all intracranial neoplasms and predominantly affect individuals of working age. Gliomas are characterized by infiltrative growth, absence of clear anatomical boundaries, high recurrence rates, and pronounced angiogenesis, especially in high-grade forms. This review summarizes current concepts of glioma classification based on tumor localization, histogenesis, and degree of malignancy according to the World Health Organization criteria. Modern diagnostic approaches, including advanced neuroimaging techniques, as well as contemporary surgical, radiotherapeutic, and chemotherapeutic treatment strategies, are discussed. Particular attention is paid to intraoperative technologies aimed at increasing the radicality and safety of tumor resection. Despite ongoing progress, the treatment of gliomas remains limited in effectiveness, highlighting the need for further research and development of novel therapeutic approaches in neuro-oncology.